Racial Inequalities: Global And National Perspectives - Marcus, Benny (TRAILS: Teaching Resources and Innovations Library for Sociology, 2012)
This course introduces you to the sociological study of racial and ethnic relationships. In the first section of the course, "Foundations," we overview racial and ethnic inequalities (and equalities) and basic concepts and theories of race and ethnicity. In the next section, we investigate the origins of racial inequalities, ideologies, and practices: European colonialism, the conquest of Native Americans, and the enslavement of Africans. For the rest of the course, we analyze how social processes, especially struggles between racially dominant and subordinate peoples, have generated changes and continuities in racial inequalities, ideologies, and practices. In the second and third sections of the course ("Colonialism, Conquest, and Slavery" and "From Abolition to Globalization"), we focus geographically on the world, primarily Europe, Africa, and the Americas. In the fourth, last, and longest section, we focus on racial and ethnic relations in the contemporary United States.